The role of innovation and agglomeration for employment growth in the environmental sector - Horbach, Jens; Janser, Markus (Nürnberg, 2015)
"The environmental sector is supposed to yield a dual benefit: its goods and services are intended to help to tackle environmental challenges and its establishments should create new jobs. However, it is still unclear in empirical terms whether that really is the case. This paper investigates whether employment growth in 'green' establishments with 'green' products and services is higher compared to other establishments. Furthermore, the main factors determining labor demand in this field are analyzed. We use linked employment and regional data for Germany. The descriptive results show that the environmental sector is characterized by disproportionately high employment growth. The application of both a generalized linear mixed model and an instrumental variables regression reveals that especially innovation and industry agglomeration foster employment growth in establishments in the environmental sector. Establishments without green products and services show a smaller increase in employment, even if they are also innovative."